2006
DOI: 10.1037/0033-2909.132.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in temperament: A meta-analysis.

Abstract: The authors used meta-analytical techniques to estimate the magnitude of gender differences in mean level and variability of 35 dimensions and 3 factors of temperament in children ages 3 months to 13 years. Effortful control showed a large difference favoring girls and the dimensions within that factor (e.g., inhibitory control: d ϭ Ϫ0.41, perceptual sensitivity: d ϭ Ϫ0.38) showed moderate gender differences favoring girls, consistent with boys' greater incidence of externalizing disorders. Surgency showed a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

94
648
15
28

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 958 publications
(785 citation statements)
references
References 197 publications
(139 reference statements)
94
648
15
28
Order By: Relevance
“…However, these often tacit expectations regarding gender specific behaviours may have an important role on teacher's ratings. Indeed, teachers' ratings have been shown to be more gender typed than are parents' ratings, and it has been suggested that this may result from teachers' frequent observations of students' interactions among same gendered students, which in turn, have shown to magnify gender role differences (Else-Quest et al, 2006;Maccoby, 1990). The strengths of the present study are as follows.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, these often tacit expectations regarding gender specific behaviours may have an important role on teacher's ratings. Indeed, teachers' ratings have been shown to be more gender typed than are parents' ratings, and it has been suggested that this may result from teachers' frequent observations of students' interactions among same gendered students, which in turn, have shown to magnify gender role differences (Else-Quest et al, 2006;Maccoby, 1990). The strengths of the present study are as follows.…”
Section: Discussionmentioning
confidence: 87%
“…This difference may result from cultural expectations, i.e. depending on the cultural gender role norms, some behavioural tendencies may be viewed as more or less appropriate or desirable in girls and boys (see meta-analysis and review by (Else-Quest, Hyde, Goldsmith, & Hulle, 2006;McIntyre & Edwards, 2009). For example, higher motor activity and aggressive tendencies may be better condoned among boys whereas silent and persistent working may be more expected from girls.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research on temperament, significant gender differences have been reported for boys scoring higher than girls on surgency/extraversion and lower than girls on effortful control or attention regulation (Else-Quest et al, 2006). Boys have also been reported to score higher on task-avoidant behaviors (e.g., Onatsu-Arvilommi & Nurmi, 2000), whereas helpless behaviors or passive avoidance may be more common to girls (Dweck, 1986).…”
Section: Temperament Affects and Behaviors 18mentioning
confidence: 96%
“…There are no significant outliers for any of the group. Research such as Else-Quest et al [12] had different conclusions when it comes to procrastination and influence of gender on it. Majority of researchers concluded that procrastination is weakly associated with males.…”
Section: Gendermentioning
confidence: 99%